Eco-friendly weed management strategies on weed dynamics, growth and yield of transplanted rice - Pooja, K; Anandan, P; Natarajan, S; Sundari, A; Saravanan, K (Plant Science Today, 2026)
A field experiment was conducted during the kharif seasons of 2024–2025 at the Experimental farm, Department of Agronomy, Annamalai University to evaluate eco-friendly weed management strategies on weed dynamics, growth and yield of transplanted rice (Oryza sativa L.). The experiment was laid out in a split plot design with 3 replications. Treatments combinations comprised of 3 stale seed bed (SSB) practices in the main plots: normal seed bed, stale seed bed for 7 days and stale seed bed for 14 days and 4 weed management practices in the sub plots: hand weeding twice at 15 and 35 days after transplanting (DAT), cono-weeding twice at 15 and 35 DAT, application of azolla 250 kg ha-1 on 3 DAT followed by cono-weeding on 35 DAT and a weedy check. Both stale seedbed methods and weed management practices exerted a significant influence on crop growth and yield of transplanted rice. Among the SSB methods, the stale seedbed technique with 14 days of weed flush prior to planting recorded the highest weed control efficiency (WCE), enhanced crop growth and resulted in superior grain yield. Among the weed management practices, hand weeding twice at 15 and 35 DAT achieved the maximum WCE and yield, which was followed by application of azolla 250 kg ha-1 on 3 DAT followed by cono-weeding on 35 DAT.